2019
DOI: 10.1530/rep-17-0734
|View full text |Cite
|
Sign up to set email alerts
|

Do Prenatal Exposures Pose a Real Threat to Ovarian Function? BPA as a Case Study

Abstract: Fetal development represents a time of potential vulnerability due to rapid cell division, organ development and limited fetal kidney/liver activity for detoxification and metabolism of exposures. Health effects of prenatal toxicant exposure have previously been described, but there is little cohesive evidence surrounding effects on ovarian function. Using bisphenol A (BPA) as a case study, we seek to examine whether a prominent prenatal environmental exposure can pose a real threat to human ovarian function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Several animal studies have strongly linked BPA exposure to follicle depletion, and this effect is observed regardless of whether exposure occurs in utero, postnatally or during adulthood (reviewed in Richardson et al 2014). Consequently, some countries have implemented bans on BPA use based on these animal studies, as human data on the reproductive consequences of BPA remain scarce (Richardson et al 2014, Mathew & Mahalingaiah 2019. Coincidently, in a study of infertile women, those with higher than average urinary BPA were identified as having a decreased ovarian reserve, and another study explored IVF outcomes for women with higher serum BPA and observed lower pregnancy rates and higher association with miscarriage (Sugiura-Ogasawara et al 2005, Lamb et al 2008.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Several animal studies have strongly linked BPA exposure to follicle depletion, and this effect is observed regardless of whether exposure occurs in utero, postnatally or during adulthood (reviewed in Richardson et al 2014). Consequently, some countries have implemented bans on BPA use based on these animal studies, as human data on the reproductive consequences of BPA remain scarce (Richardson et al 2014, Mathew & Mahalingaiah 2019. Coincidently, in a study of infertile women, those with higher than average urinary BPA were identified as having a decreased ovarian reserve, and another study explored IVF outcomes for women with higher serum BPA and observed lower pregnancy rates and higher association with miscarriage (Sugiura-Ogasawara et al 2005, Lamb et al 2008.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…For example, in pregnant ewes, the expression of fetal ovarian microRNAs is modified by exposure to BPA from Days 30 to 90 of gestation, leading to changes in developmental and functional insulin-related genes (Veiga-Lopez et al 2013). This observation builds on extensive literature suggesting that the prenatal fetal ovary is particularly sensitive to BPA, in both human and animal models, and that low BPA concentrations affect the epigenome of female germ cells in rodents (Eichenlaub-Ritter and Pacchierotti 2015; Chianese et al 2018;Mathew and Mahalingaiah 2019;Huang and Zeng 2021). The effects of environmental contaminants can also be transgenerational, although to date the most emphatic demonstration has been with rodent models.…”
Section: Environmental Contaminantsmentioning
confidence: 79%
“…Notably, this impact has been consistently found irrespective of the timing of exposure, whether it occurred during the prenatal period, postnatal period, or in adulthood (Richardson et al, 2014). As a result, numerous countries have enacted restrictions on the usage of BPA based on evidence derived from animal studies, given the inconclusive nature of available human data about the reproductive impacts of BPA (Richardson et al, 2014;Mathew & Mahalingaiah, 2019). A study conducted on women experiencing infertility revealed that individuals with urinary BPA levels exceeding the average demonstrated a diminished ovarian reserve.…”
Section: Environmental Factorsmentioning
confidence: 99%